BASLAWÍSH KLASS ANA TILI SABAQLARÍNDA OQÍWSHÍLARDÍŃ SÓZLIK BAYLÍĠÍN ARTTÍRÍWDA OYÍN USÍLLARÍNAN PAYDALANÍW - Kenesova, B.S. (SCIENCE and SOCIETY, 2023)
Today in our country a lot of attention is paid to the educational process, in particular, the education of students and the motivation of teachers who teach them. That puts a lot of responsibility on teachers. This article focuses on the significance of using games in the effective organization of mother tongue lessons.